Elastic fibers: formation, function, and fate during aging and disease. (10th May 2021) - Schmelzer, Christian E. H.; Duca, Laurent
Abstract : Elastic fibers are extracellular components of higher vertebrates and confer elasticity and resilience to numerous tissues and organs such as large blood vessels, lungs, and skin. Their formation and maturation take place in a complex multistage process called elastogenesis. It requires interactions between very different proteins but also other molecules and leads to the deposition and crosslinking of elastin's precursor on a scaffold of fibrillin‐rich microfibrils. Mature fibers are exceptionally resistant to most influences and, under healthy conditions, retain their biomechanical function over the life of the organism. However, due to their longevity, they accumulate damages during aging. These are caused by proteolytic degradation, formation of advanced glycation end products, calcification, oxidative damage, aspartic acid racemization, lipid accumulation, carbamylation, and mechanical fatigue. The resulting changes can lead to diminution or complete loss of elastic fiber function and ultimately affect morbidity and mortality. Particularly, the production of elastokines has been clearly shown to influence several life‐threatening diseases. Moreover, the structure, distribution, and abundance of elastic fibers are directly or indirectly influenced by a variety of inherited pathological conditions, which mainly affect organs and tissues such as skin, lungs, or the cardiovascular system. A distinction can be made between microfibril‐related inherited diseases that are the result of mutations in diverse microfibril genes and indirectly affect elastogenesis, and elastinopathies that are linked to changes in the elastin gene. This review gives an overview on the formation, structure, and function of elastic fibers and their fate over the human lifespan in health and disease. Abstract : Elastic fibers are vital extracellular components of vertebrates providing numerous tissues and organs with the elasticity and resilience required for their function. Here, we review the current knowledge and discuss open questions on the formation, structure, and functions of elastic fibers and how aging and diseases affect their fate over the human lifespan.